The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1515/mammalia-2011-0039
|View full text |Cite
|
Sign up to set email alerts
|

Home range size and habitat selection of Geoffroy’s cat (Leopardus geoffroyi, Felidae, Carnivora) in the pampas grassland

Abstract: This study examined the spatial ecology of Geoffroy ' s cats, Leopardus geoffroyi, living in a protected area surrounded by croplands in the Argentine grasslands. A total of six different adults were marked with 14 radio-collars from 2001 to 2005 but only three (one female and two males) produced a meaningful amount of data (54-135 positions). Total home range size was 8.83 ± 1.58 km 2 (100 % Minimum Convex Polygon) and 7.27 ± 2.23 km 2 (90 % Fixed Kernel). Core areas averaged 1.46 ± 0.84 km 2. Geoffroy ' s ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The native grasslands of Río de la Plata grasslands region support several mammal species, such as the Molina's hog-nosed skunk (Conepatus chinga) (Castillo et al 2011, 2012), the Coypu (Myocastor coypus) (Guichon and Cassini 1999), Geoffroy's cats (Oncifelis geoffroyi) (Manfredi et al 2006(Manfredi et al , 2012) and short-tailed opossum (Monodelphis dimidiata) (Baladrón et al 2012). Landscape perturbation and land use change had different effects on the diversity, abundance, and distribution of rodent species depending on the initial fragmentation status of the landscape.…”
Section: Animal Diversitymentioning
confidence: 99%
“…The native grasslands of Río de la Plata grasslands region support several mammal species, such as the Molina's hog-nosed skunk (Conepatus chinga) (Castillo et al 2011, 2012), the Coypu (Myocastor coypus) (Guichon and Cassini 1999), Geoffroy's cats (Oncifelis geoffroyi) (Manfredi et al 2006(Manfredi et al , 2012) and short-tailed opossum (Monodelphis dimidiata) (Baladrón et al 2012). Landscape perturbation and land use change had different effects on the diversity, abundance, and distribution of rodent species depending on the initial fragmentation status of the landscape.…”
Section: Animal Diversitymentioning
confidence: 99%
“…4) Because the Pampas fox is the most ecologically adaptable species of the carnivore guild of the Espinal, we expected that it would show a less marked response to landscape composition than more selective species, such as Geoffroy’s cat. 5) Based on what is known by their respective habitat preferences, we expected that skunks would make intensive use of croplands located in proximity of comparatively more densely vegetated patches [ 36 , 37 ], whereas Geoffroy’s cat would show an association with the habitat with the densest cover of natural vegetation, namely the shrubland [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there seems to be a limit to this adaptability (Castillo et al, 2008), since totally open areas such as dry grasslands appear to be unsuitable (Caruso et al, 2016;Manfredi et al, 2012). In this study, we observed that this Geoffroy"s cat population did not use environmental resources uniformly, selecting areas that were more distant from roads and closer to water and native forest.…”
Section: Discussionmentioning
confidence: 67%